DESIGN OF FUZZY CONTROL OF WASTEWATER TREATMENT PROCESSES - COSTACHE (BIRA) Lenuta (Fiabilitate şi Durabilitate)
This paper presents how to use in processes the wastewater treatment and the control processes using direct fuzzy control of the process , fuzzy supervision of classic PID regulators and how fuzzy adaption of clasic PID controller. I also mentioned about fuzzy control design for water treatment following steps fuzzification and defuzzification.